Clinical, Pathological and Haematological Effects of Micrococcus Infections in Rainbow Trout (Oncorhynchus mykiss Walbaum - Aydın, Seyit; Çiltaş, Abdülkadir; Yetim, Hasan; Akyurt, İhsan (Journal of Animal and Veterinary Advances 4 (2) : 167 - 174, 2005)
This study investigates chronic and sporadic Micrococcus luteus infections of 3 and 4 -year-old broodstock and 2-year- old juvenile cultured rainbow trout (Oncorhynchus VValbaum) during February through April 1 993-1996. Infection had not been observed from 1 997 to 2003. Bacterial isolates vvere identified each year and were tested to determine sensitivity to chemotherapeutants. Infections caused lesions on the skin and caudal fin, and internal organs such as muscle, liver and spleen. In 1 995, naturally infected 2-year-old fish were examined for haematological variables and compared to healthy fish. Leucocytosis and thrombocytosis occurred as well as a reduction in haemoglobin and haematocrit values of infected fish. In 1 996, histopathological examination demonstrated pathological changes in heart, liver, spleen, gill, muscle, kidney and intestinal tissues of juvenile rainbow trout. The minimum bactericidal concentrations (MBCs) of formalin (90 0/0) ethyl alcohol (1 0 0/0) mixture and enrofloxacin against pathogenic bacterium isolated in 1 996 were 3 ug/ml and 0.025 og/ml, respectively. Formalin + ethyl alcohol mixture baths and oral applications of enrofloxacin vvere successfully used for the treatment of naturally infected fish in 1996. Pathogenicity of the M. luteus isolated from crucian carp (Carassius carassjus L.) was tested by intramuscular injection using healthy rainbow trout.
Keywords: Disease, rainbow trout, Micrococus luterus, haematology, treatment; Clinical, Pathological and Haematological Effects of Micrococcus Infections in Rainbow Trout (Oncorhynchus mykiss Walbaum